Hubungan Efikasi Diri dengan Tingkat Kecemasan Mahasiswa dalam Mengerjakan Tugas Skripsi di Fakultas Kedokteran UNIMUS - Monalisa Rossa Hidayati; Suprihhartini Suprihhartini; Nanik Marfu’ati (Universitas Respati Indonesia, 2026)
Background: The pressure and demands of writing a thesis can cause anxiety. These feelings are limited by fear and discomfort, and are usually accompanied by autonomic side effects. Anxiety is common among medical students. Therefore, students need to be instilled with confidence in their abilities so that they are confident in their ability to complete every requirement that must be fulfilled. This is called self-efficacy. Method: The study was conducted in November 2023, with a quantitative observational (non-experimental) research design using a cross-sectional approach. The tools and materials used were questionnaire Zung Self-Assessment Anxiety Scale (ZSAS) and the General Self-Efficacy Scale (GSES). The research sample consisted of 66 final-year undergraduate students from the Faculty of Medicine at UNIMUS, class of 2020, selected through simple random sampling. Data analysis used the Spearman's rank correlation test, with significance set at p